Clinical Effectiveness, Safety and Tolerability of Amlodipine/Valsartan in Hypertensive Patients: the Indonesian Subset of the EXCITE Study - Arini Setiawati; Harmani Kalim; Arif Abdillah (Acta Medica Indonesiana)
Aim: to assess the effectiveness, safety and tolerability of amlodipine/valsartan (Aml/Val) single-pill combination (SPC) in hypertensive patients in a real-world setting. Methods: the Indonesian subset of the EXCITE (clinical EXperience of amlodIpine and valsarTan in hypErtension) study, which was a multinational, prospective, observational, open study in hypertensive patients treated with Aml/Val SPC for 26 weeks. Aml/Val SPCs (5/80, 5/160, 10/160 mg) were administered as monotherapy or as add-on therapy to other antihypertensive medications in patients not controlled by prior monotherapy. The effectiveness outcomes were (1) mean decrease in sitting systolic blood pressure and diastolic blood pressure (msSBP and msDBP) from baseline to week 26; (2) proportion of patients achieving BP goal (<140/90 mmHg for nondiabetics, or <130/80 mmHg for diabetics); (3) proportion of patients who were responders (achieving BP goal or BP reduction of >20/10 mmHg). The safety variables were the incidence of AEs and SAEs, and the incidence of edema. Results: a total of 500 patients from Indonesia received Aml/Val SPC, 487 patients were analyzed for efficacy (by LOCF), and 464 patients completed the study. At study end (week 26), the overall msSBP and msDBP(95% CI) reductions from baseline were -33.7(-35.2, -32.1) mmHg and -14.8 (-15.7, -13.8) mmHg, respectively. Among the 487 patients, 52.4% achieved BP goal and 80.5% were responders (LOCF). Among 464 patients who completed the study, 53.7% achieved BP goal and 84.5% were responders. Aml/Val SPC was effective in decreasing BP in Indonesian patients. AEs, including SAEs, were reported in 11.4% patients, with SAEs in 1% of patients, and death in 0.8% of patients. SAEs and deaths were considered unrelated to the study drug. Edema was reported by 9.4% of patients at baseline, and in 3.7% patients at end of study. Effectiveness, tolerability and compliance were rated good and very good in 90.8%, 92.2%, and 89.2% of patients, respectively, according to the investigators. Conclusion: Aml/Val SPC was effective for BP reductions and well tolerated in hypertensive patients, not adequately controlled by monotherapy, in a daily clinical setting in Indonesia.